Flood prevention through zoning system in Baduy local wisdom - Nisrinah; Herdiansyah, Herdis (Journal of Socio-Cultural Sustainability and Resilience, 2024)
Background: Flooding is frequent disasters faced by the majority of regions in Indonesia. One cause of the flooding was the fault of urban and regional planning. Need a good regional plan to prevent flooding. Method: The study reviews existing literature on the Baduy tribe's zoning system and local knowledge to understand its role in flood risk management. It examines how these traditional practices, as discussed in previous research, contribute to preventing and mitigating flooding. Findings: Community participation is very influential in maintaining natural ecosystems. Baduy tribes live in the village of Kanakes, Banten Province. Baduy tribe held the belief that it is called by the Sunda wiwitan. That trust is called pikukuh customs regulations. Pikukuh contains the prohibition for a change; it can be seen from the utterances in pikukuh. The utterance meaning related to the relationship between humans and the environment. Relationships are not always good for the environment. Negative impacts could be catastrophic that can harm humans themselves. The role of the community can be influenced by the prevailing local wisdom in the area. One of the tribes that still apply local knowledge is Baduy. Local knowledge of Baduy tribe-related issues through the use of the applicable zoning area. Zone area of the Baduy tribe is divided into three zones, namely a third or upper zone, a second zone or central zone and the first zone or the lower zone. The results of this study indicate that the zoning system applied to the wisdom of the Baduy tribe workshops can prevent flooding The importance of forests in minimizing erosion. Forests in the third zone or upper zones serve to catch the falling water flow from upstream, reducing the water flowing downstream. They also help retain soil material during rainfall, further preventing erosion. This analysis underscores the intricate relationship between local practices, environmental conservation, and sustainable development. Conclusion: In conclusion, the Baduy tribe’s zoning system is a testament to their deep understanding of their environment and their commitment to living in harmony with nature. It highlights the importance of local wisdom in managing natural resources and mitigating environmental risks. As we grapple with the increasing threat of climate change and environmental degradation, there is much to learn from the Baduy tribe’s sustainable practices and profound respect for nature. Novelty/Originality of this article: This study uniquely examines the Baduy tribe's traditional zoning system as an effective flood prevention strategy, offering valuable insights into how indigenous knowledge can be integrated into modern environmental management and disaster risk reduction practices.